2002
DOI: 10.1074/jbc.m111428200
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Protects against Oxidative Stress via Inactivation of the c-Jun N-terminal Kinase Stress-signaling Pathway in Neuronal Cells

Abstract: The expression of ␣-synuclein, a synaptic molecule implicated in the pathogenesis of neurodegenerative disorders such as Parkinson's disease and Lewy body disease is increased upon injury to the nervous system, indicating that it might play a role in regeneration and plasticity; however, the mechanisms are unclear. Because c-Jun N-terminal kinase (JNK), a member of the mitogen-activated protein kinase family, plays an important role in stress response, the main objective of the present study was to better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
2
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(137 citation statements)
references
References 58 publications
4
129
2
2
Order By: Relevance
“…This result is in accordance with our previous findings showing that induction of apoptosis by TNFa in EW7 cells required a prolonged activation of JNK (Javelaud and Besancon, 2001). In agreement with our observations, activation of JNK by H 2 O 2 and its role in induction of apoptosis was reported in cardiomyocytes (Aoki et al, 2002) and neuronal cells (Hashimoto et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in accordance with our previous findings showing that induction of apoptosis by TNFa in EW7 cells required a prolonged activation of JNK (Javelaud and Besancon, 2001). In agreement with our observations, activation of JNK by H 2 O 2 and its role in induction of apoptosis was reported in cardiomyocytes (Aoki et al, 2002) and neuronal cells (Hashimoto et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, transfection of cells with a vector encoding a dominant-negative form of JNK1 reduced apoptosis in 2-Me-treated cells as compared to cells transfected with an empty pcDNA vector (Figure 9b). This result (Benhar et al, 2001;Aoki et al, 2002;Hashimoto et al, 2002). We therefore investigated whether generation of H 2 O 2 that occurred in 2-Me-treated cells was responsible for JNK activation.…”
Section: Activation Of the Map Kinases Erk1/2 And Jnk By 2-mementioning
confidence: 97%
“…[25][26][27] In this study, we extended these observations by demonstrating the presence of IB1/JIP-1 in human AD brain colocalized with JNK and phosphorylated tau proteins in neurofibrillary tangles. IB1/JIP-1 interacts with many cellular components including the reelin receptor ApoER2, LRP, a-synuclein, 190 RhoGEF, kinesin and APP [13][14][15][16][17][18]40 . In mice, the selective disruption of both ApoER2 and VLDL receptor (VLDLR) induced a drastic phenotype associated with abnormal neuronal migration and development.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were done in quadruplicate and statistically analyzed by Student's t test. Trypan blue exclusion assays were performed as previously described (23).…”
Section: Methodsmentioning
confidence: 99%
“…The precise physiological role of ␣-and ␤-synuclein in synaptic plasticity is not completely understood. However, recent studies have demonstrated that although ␣-synuclein is aggregated under oxidative stress conditions, ␤-synuclein does not aggregate to form amyloid fibrils, and it is capable of blocking ␣-synuclein aggregation and potentially protecting cells from the neurotoxic effects of ␣-synuclein oligomers (23,24). The mechanisms by which ␣-synuclein accumulation might lead to neurodegeneration are currently under investigation.…”
mentioning
confidence: 99%